The Role of Exosomes in Thyroid Cancer and Their Potential Clinical Application - Feng, Kaixiang; Ma, Runsheng; Zhang, Lele; Li, Hongqiang; Tang, Yifeng; Du, Gongbo; Niu, Dongpeng; Yin, Detao (Frontiers in Oncology, 2020)
The incidence of thyroid cancer is rapidly increasing worldwide. The diagnostic accuracy and dynamics of thyroid cancer need to be improved, and traditional treatments are not effective enough for patients with poorly differentiated thyroid cancer. Exosomes are membrane vesicles secreted specifically by various cells and are involved in intercellular communication. Recent studies have shown that exosomes secreted by thyroid cancer cells contribute to tumor progression, angiogenesis and metastasis. Exosomes in liquid biopsies can reflect the overall molecular information of tumors, and have natural advantages in diagnosing thyroid cancer. Exosomes also play an important role in tumor therapy due to their special physicochemical properties. Thyroid cancer patients will benefit as more exosome patterns are discovered. In this review, we discuss the role of thyroid cancer-derived exosomes in tumorigenesis and development, and describe the application of exosomes in the diagnosis and treatment of thyroid cancer.